Open Access and Its Implications for the Dissemination of Scientific Knowledge - Ni Ketut Gita Saraswati; Astuti Wijayanti; I Gusti Ayu Putri Trisnayanti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The development of information technology has transformed the dissemination of knowledge globally. The Open Access (OA) movement emerged as a fundamental response to democratize scientific access and break down the financial barriers (paywalls) adopted by conventional publishing models. Trends over the past decade have shown a clear paradigm shift, with an increase in Gold Open Access articles from 11% to 38%, and a 47% increase in citations for OA articles compared to paid articles. Nevertheless, the implications of OA for the overall dissemination of knowledge, including aspects of affordability, visibility, citation impact, equality of access, and its relationship to digital literacy, still require in-depth synthesis. This study aims to map, analyze, and synthesize findings from previous research on the development of Open Access and its comprehensive implications for the knowledge dissemination ecosystem. This study uses a systematic literature review method. Data were collected through a review of various literature, regulations, and data related to the trends and impacts of Open Access implementation over a relevant timeframe. Open Access has significant positive implications for accelerating the dissemination of knowledge and improving global digital literacy. This literature synthesis emphasizes the importance of policy support and strengthening open access journal governance to create equitable, inclusive, and sustainable access to science.